Respuesta del cultivo de girasol (Helianthus annuus L.) a la aplicación de dos bioestimulantes orgánicos en la zona de Pangua. - Garófalo León, Iván Darío (2017)
The present study was carried out with the purpose of evaluating the effect of the application of two biostimulants in three doses on the crop of sunflower (Helianthus annuus L.) planted in the area of Pangua. For this purpose, the trial was established on lands of the ““Ernestina”” estate, owned by Mrs. Adela Salazar Gaibor, located at Km 25 of the Quevedo - Moraspungo road, between coordinates 1 ° 04'35.4 "S 79 ° 18 ' 26.3 "W, at an altitude of 147 meters above sea level. A randomized complete block design with 2x3 + 1 factorial arrangement was used in three replicates, studying the biostimulants Basfoliar Algae and Basfoliar Aktiv, in three doses: 1.0, 1.5 and 2.0 l / ha, whose interactions were compared with a control without application of Biostimulants. Percentage data of plants with rootstock, plant height at harvest (cm), chapter diameter (cm), chapter weight (g) and yield per hectare (kg) were recorded. As main results it was observed that the biostimulants and doses did not significantly influence the percentage of plants in the root bed and weight of 100 seeds. The plants with the highest height (140.0 cm), chapter weight (156.2 g) and higher yield (4604.8 kg / ha) were recorded at the dose of 2.0 l / ha. The biostimulant Basfoliar Algae produced plants taller than 2.6 cm, 0.7 cm larger, 4.6 g heavier and 212.1 kg / ha yield than Basfoliar Aktiv. The biggest economic benefit was registered with the application of 2.0 l / ha of Basfoliar Algae which generated a net income of $ 621.76, with a profitability of 48%.